pink3343
pink3343
04-01-2018
Mathematics
contestada
Can someone help me with this??
Respuesta :
Аноним
Аноним
05-01-2018
–6(x – 2y) when x = –3 and y = –5
so
–6(x – 2y)
=
–6(-3 – 2(-5))
= -6(-3 + 10)
= -6(7)
= -42
answer
A. -42
Answer Link
VER TODAS LAS RESPUESTAS ( 75+ )
Otras preguntas
Select the correct text in the passage. Which are Jordan’s short-term goals?
The formula Upper V equals LWH is used to find the volume of a box. If the length of a box is increased 4 times, the width is increased 4 times, and the heigh
A 110 point final exam is made up of 50 questions. Some questions are worth 2 points and some are worth 4 points. How many of each type of question are on the t
Solve for x. x² + 6x + 9 = 12 x=−9±4 √3 x=−3±4 √3 x=−9±2 √3 x=−3±2 √3
Drag a statement or reason to each box to complete this proof. If −3(x+8)=−21, then x=−1.
I am Oscar from Miami, and yesterday I lost a tooth playing soccer. Last night I put my tooth under my pillow, and this morning it was gone! The tooth fairy had
What is the origin of music? (How, where, when and who) I’ll brainliest who answers the four questions
The difference between a manifest function and a latent function is that a manifest function has an __________ beneficial consequence and a latent function has
What is the average distance in microns an electron can travel with a diffusion coefficient of 25 cm^2/s if the electron lifetime is 7.7 microseconds. Three sig
Which group of people describes who the palestinians are today living in the middle east and originally from palestine (or can trace their ancestry back to pale